HUBUNGAN ANTARA KETERLIBATAN KERJA DAN KEPUASAN KERJA DENGAN PERILAKU SOSIAL ORGANISASI DOSEN TETAP FKIP UNIVERSITAS ISLAM RIAU PEKANBARU - Shinta Stephani; RR. Sri Kartikowati; Fadly Azhar (Universitas Riau, 2017)
The purpose of this study was to analyze the relationship between job involvementand job satisfaction with the Organizational Citizenship Behavior.This research was conductedin faculty of education Islamic University of Riau Pekanbaru.This is a survey reserch. Thepopulation was 103 lecturers wich was taken as sample totally 82 using simple random samplingtechnique. Instruments used to collect data was corrective using instrument over 3 variablethan data was analyze using Product Momentand Alpha Cronbachformulas. The reserch found1)there isasignificant relationship between Job Involvement (x1) with the Organizational CitizenshipBehavior (y) with the coefficient of determination 0,553. 2)there is a significant relationship ofJob Satisfaction (x2) with the Organizational Citizenship Behavior (y) with the coefficient ofdetermination 0.381.3. 3)there is a significant relationship of Job Involvement (x1) and JobSatisfaction (x2) with the Organizational Citizenship Behavior (y) with the coefficient ofdetermination 0,644. The conclusion of the study shows that the Organizational CitizenshipBehavior can be improved through Job Involvement and Job Satisfaction.